If You Build It, Will They Come? School Availability and School Enrollment in 21 Poor Countries - Filmer, Deon (World Bank, Washington, D.C., 2013)
Increasing the supply of schools is commonly advocated as a policy intervention to promote schooling. Analysis of the relationship between the school enrollment of 6 to 14 year olds and the distance to primary and secondary schools in 21 rural areas in low-income countries (including some of the poorest countries in Sub-Saharan Africa) reveals that the two are often statistically significantly related. However, the magnitudes of the associations are small. Simulating big reductions in distance yields only small increases in average school participation, and only small reductions in within-country inequality. The data are mostly cross-sectional and therefore it is difficult to assess the degree to which results might be driven by endogenous school placement. Data can be geographically matched over time in three of the study countries and under some assumptions the results from these countries are consistent with no substantial bias in the cross-sectional estimates. Although increasing school availability by decreasing the average distance to schools can be a tool for increasing enrollments, it cannot be expected to have a substantial effect. Other interventions, such as those geared toward increasing the demand for schooling or increasing the quality of schooling should be prioritized.